EDUCATIONAL COMPUTER PROGRAM FOR DESIGN OF BUILDING COMPONENTS ACCORDING TO IS:456-2000 - VINOD KUMAR, A.; AKHIL, TEJ; CHAKALI, BALA HUSSAINY; SYED, AFZAL BASHA (I-Manager's Journal on Information Technology, 2020)
The design of reinforced cement concrete is very important subject for students as well as engineers. Reinforced concrete design is very complex and repetitive in nature for neophyte students to understand practical aspects in construction. In order to overcome this problem, suitable tool is required. In this paper an educational software which is created in visual basic 6.0 is presented for students which is user friendly and robust in nature for day-to-day works in site. After using this educational software many students expressed their appreciation about their understanding in reinforced concrete design. The graphical user interface (GUI) of the programs developed in this software is also presented in this paper.